Development of Accounting System of Occupation Group Ban Nongkahoo Amphur Muangtak - จันทร์แก้ว, ยุพรัตน์ (Community and Social Development Journal, 2015)
This research aimed to develop accounting system of occupation group Ban Nongkahoo Amphur Muangtak. The collecting data, the questionnaires were used from six persons of purposive sampling. Description statistics of percentage, mean and standard division were used to analyze the data. Studying an old accounting system result of occupation group found that the group used one notebook for writing trades list and only someday, had to take cash account of received cash and pay cash. Results of an account document, an account book, a control register had not make and the document for recording account did not make. Method of a storing document used pinching the document with the account book and a financial report did not make. This reason, an administration and a true finance of the occupation group could not know. Therefore, researcher developed the appropriated accounting system with business of the occupation group in 5 accounting systems. They were 1) account systems of product buy and package, 2) a pay account system, 3) a production account system, 4) a product sale account system and 5) a cash account system. The accounting document, the account book, the control register and designing the need financial report and administration report of business were developed. Research results from achievement and contentment of users from development account system found that the achievement and the contentment of 5 account systems including development the accounting document, the account book, the control register and the financial report were well level. The overall image results of studying development account system were well level.